Implemetasi manajemen risiko dalam perbankan syariah di Indonesia - Azkya, Vaizul (Maliki Interdisciplinary Journal, 2025)
The growth of Islamic banking in Indonesia presents significant challenges due to various inherent risks in its operational activities. Risk-taking is an integral part of decision-making, thus systematic and professional risk management is crucial to maintaining the stability and sustainability of Islamic banks. This study qualitatively examines risk management implementation in Islamic banking, referring to regulations by the Financial Services Authority (OJK) and the Islamic Financial Services Board (IFSB). Risks faced are categorized into financial risks such as credit, market, liquidity, rate of return, and investment risks, as well as non-financial risks including operational, legal, compliance, and reputational risks. Risk management implementation involves integrated stages of risk identification, measurement, monitoring, and control. The success of risk management depends on leadership commitment, regulatory compliance, and effective use of information technology. Effective risk management enables Islamic banks to improve performance, uphold Shariah principles, and strengthen competitiveness amid intense industry competition.